1990
DOI: 10.1007/bf00047064
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of indentation cracks near free surfaces and interfaces

Abstract: The purpose of this research was to examine problems associated with the propagation of cracks near a free surface and near the interface of a glass/epoxy bonded system. Crack propagation was induced by placing Knoop indentations in the glass at various sites adjacent to and remote from the surface or interface. These experimental studies were supplemented by finite element stress analysis. Experiments show that for an indent parallel to the surface or interface, the initial direction of crack propagation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…However, the magnitude of increase was less than that for the crack running perpendicular to the interface. The crack running near parallel to the interface deflects under the influence of the elastic mismatch, as previously described 13) . Based on these considerations, the transverse radial cracks were most suitable for this investigation.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, the magnitude of increase was less than that for the crack running perpendicular to the interface. The crack running near parallel to the interface deflects under the influence of the elastic mismatch, as previously described 13) . Based on these considerations, the transverse radial cracks were most suitable for this investigation.…”
Section: Discussionmentioning
confidence: 98%
“…The degree of crack slanting was greater for smaller marginal angles and shorter distances from the ceramic/resin interface. Several studies have reported on crack slanting or deflection in ceramic materials with a marginal angle of 90° 13,14,[22][23][24] . Crack slanting or deflection occurred with marginal angles of 45 and 60°.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations